Analisa Literatur Akuntansi Akad Musyarakah - Rizky Fauzi, Muchamad; Rizki Darmawan, Mochamad; Yuliartin, Fenty (Jurnal Perbankan Syariah, 2022)
Abstract: The development of the Islamic economic concept requires the development of other economic scientific concepts to support the development of Islamic economics. One of them is the development of sharia accounting science. Accounting records for sharia contracts require separate discussion and separate procedures because of the uniqueness of sharia contracts. This study aims to discuss the procedures for recording accounting for musyarakah contracts. Using a qualitative approach, this study examines the literature that discusses musyarakah contracts and the accounting records of musyarakah contracts. Shows that the accounting results of musyarakah contracts are divided into two, namely cash and non-cash financing. In addition, there is also a recording of declining musyarakah contracts. Do not forget to record when there are profits and losses. Abstrak: Berkembangnya konsep ekonomi syariah menuntut berkembangnya konsep keilmuan ekonomi lain untuk mendukung perkembangan ekonomi syariah. Salah satunya yakni perkembangan ilmu akuntansi syariah. Pencatatan akuntansi pada akad-akad syariah memerlukan pembahasan tersendiri dan tatacara tersendiri karena keunikan akad syariah. Penelitian ini bertujuan untuk mebahas tatacara pencatatan akuntansi untuk akad musyarakah. Menggunakan pendekatan kualitatif, penelitian ini menelaah literatur yang membahas menganai akad musyarakah serta pencatatan akuntansi akad musyarakah. Menunjukkann hasil pencatatan akuntansi akad musyarakah dibedakan menjadi dua yakni pembiayaan kas dan non kas. Selain itu juga terdapat pencatatan akad musyarakah menurun. Tidak lupa pencatatan ketika terjadi keuntungan dan kerugian.